2010
DOI: 10.1111/j.1439-0396.2010.01009.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with carnosine improves antioxidant capacity and meat quality of finishing pigs

Abstract: This study was conducted to determine the effect of dietary carnosine (β-alanyl-L-histidine) supplementation on antioxidant capacity and meat quality of pigs. 72 pigs approximately 60 kg were fed a corn- and soybean meal-based diet supplemented with 0, 25, 50 or 100 mg carnosine per kg diet for 8 weeks. Carnosine supplementation did not affect growth performance and carcass traits of pigs. However, the addition of 100 mg carnosine per kg diet increased pH value of muscle at 45 min, 24 h and 48 h postmortem. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 59 publications
4
37
2
Order By: Relevance
“…In the present study, dietary supplementation with carnosine significantly increased the activities of T‐AOC, GSH‐Px and T‐SOD in thigh muscle. Similarly, previous studies have found that carnosine supplementation increased the activities of T‐SOD and GSH‐Px in skeletal muscle of finishing pigs, elevated GSH‐Px activity in the liver and kidney of diabetic mice and decreased pro‐oxidant status induced by d ‐galactose in the liver of rats . The antioxidant action of carnosine mainly depends on chelating divalent metal ions and scavenging free radicals .…”
Section: Discussionsupporting
confidence: 57%
“…In the present study, dietary supplementation with carnosine significantly increased the activities of T‐AOC, GSH‐Px and T‐SOD in thigh muscle. Similarly, previous studies have found that carnosine supplementation increased the activities of T‐SOD and GSH‐Px in skeletal muscle of finishing pigs, elevated GSH‐Px activity in the liver and kidney of diabetic mice and decreased pro‐oxidant status induced by d ‐galactose in the liver of rats . The antioxidant action of carnosine mainly depends on chelating divalent metal ions and scavenging free radicals .…”
Section: Discussionsupporting
confidence: 57%
“…Administration of carnosine for 5 days resulted in the inhibition of micronuclei caused by CP, and it showed protective and anticlastogenic effects. [22][23][24][25] These enzymatic antioxidants have important role in reducing side effects induced by oxidative stress. The main characteristic of antioxidants is the ability to trap free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Further, treatment of beef patties with 50 mM carnosine increased a* value during a 20 d retail display and decreased both lipid and myoglobin oxidation (Sánchez-Escalante, Djenane, Torrescano, Beltrán, & Roncalés, 2001). Pigs supplemented with carnosine (100 mg/kg/d for 8 weeks) prior to slaughter found that the meat had an increased a* value following fabrication (Ma et al, 2010). Further, mRNA expression of superoxide dismutase and glutathione peroxidase was increased leading the authors to hypothesize that carnosine supplementation improves antioxidant capacity and meat quality of pigs (Ma et al, 2010).…”
Section: Color Stabilitymentioning
confidence: 97%
“…Pigs supplemented with carnosine (100 mg/kg/d for 8 weeks) prior to slaughter found that the meat had an increased a* value following fabrication (Ma et al, 2010). Further, mRNA expression of superoxide dismutase and glutathione peroxidase was increased leading the authors to hypothesize that carnosine supplementation improves antioxidant capacity and meat quality of pigs (Ma et al, 2010). Additionally, previous studies have outlined the differences between more and less color stable cuts of meats including some of the physiologic reasons believed to be responsible for these differences (Hood, 1980;Hunt & Hedrick, 1977;King, Shackelford, Rodriguez, & Wheeler, 2011;McKenna et al, 2005).…”
Section: Color Stabilitymentioning
confidence: 99%
See 1 more Smart Citation